👤
a fost răspuns

2x+7=3x-2
7x+3-3x=4x+3
2x-5+8x=10x+8
5-3x=8x+2
2+6(4x-2)=9-5(2x+3)


Răspuns :

      2x-5+8x=10x+8       5-3x=8x+2       2+6(4x-2)=9-5(2x+3)
        2x-10x+8x=5+8        8x-3x=5           2+6*2x=9-5*5x
            x=13                    5x=5 /:5           2+12x=9-25x
                                       x=1                  12x+25x=9-2
                                                                   7x=7 /:7
                                                                     x=1

2x+7=3x-22x-3x=-2-7
-x=-9    inmultim -1
x=9

7x+3-3x=4x+3
4x+3=4x+3
4x-4x=3-3
x
∈Ф

2x-5+8x=10x+8
10x-5=10x-8
10x-10x=5-8
x
∈Ф

5-3x=8x+2
-3x-8x=2-5
-11x=-3     inmultim -1
x=3/11

2+6(4x-2)=9-5(2x+3)
2+24x-12=9-10x-15
24x+10x=-6-2+12
34x=0
x=0